OPTIMAL POWER DISTRIBUTION PLANNING USING IMPROVED PARTICLE SWARM OPTIMIZATION - Kumari, Meena; Ranjan, Rakesh; Singh, VR; Swapnil, Shubham (International Journal of Intelligent Systems and Applications in Engineering, 2018)
In planning of radial power distribution system, optimal feeder routing and optimal branch conductor selection plays an important role. The highly economical distribution system requires effective planning method which involves optimization procedure to connect the given load to the substations. In this paper optimal power distribution system is presented with minimum energy loss cost for paths and optimal conductors. The proposed optimal power distribution is procedure is described in following stages, initially read the input system data and identify all the possible paths. Then for each identified path forward/backward sweep load flow technique is applied to calculate the energy loss costs and select the minimum energy loss cost path for the power distribution. Finally, the optimal branch conductor selection of radial distribution system is performed by using particle swarm optimization (PSO). Here, the optimization is improved by using the power loss and depreciation on capital investment parameters. This results the optimal conductor and then the location of optimal conductor is chosen as the optimal substation and then through the optimal substation power is distributed optimally.Â